The Effect of Parenting Patterns on the Character of Early Children (Case Study in Integrated Islamic Kindergarten Az-Zahra, Bebesen District) - Sella Ulfami, Nadia (Al'Adzkiya Journal, 2023)
This study aims to determine whether there is an effect of parenting on the character of early childhood. The formulation of the problem from this study is whether there is an influence of parenting patterns on the character of early childhood. This type of research is quantitative. The subjects of this study were the guardians of the IT Az Zahra Kindergarten students as many as 30 parents. The research data collection technique used a questionnaire, while the data analysis used simple linear regression analysis. The results obtained are t_count > t_table which is 3.940 > 2.042 so H_a is accepted while H_O is rejected, meaning that there is a significant influence between parenting and the character of early childhood in TK IT AZ ZAHRA.Keywords: Parenting, character, early childhood.